Convergent validity and sex invariant factor structure of the Movement Imagery Questionnaire-3 - Second version (MIQ-3S): Healthy, young adult reference data. (June 2022) - Monsma, Eva V.; Gregg, Melanie J.; Seiler, Brian; Sacko, Ryan S.; Hall, Craig R.
Abstract: Aligned with the approach that established the factor structure of the Movement Imagery Questionnaire-3 (MIQ-3), this study extended the two-factor structure of the Movement Imagery Questionnaire – Revised Second version (MIQ-RS). The extension involves assessment of both internal and external visual imagery abilities along with kinesthetic imagery ability. Participants (N = 396) completed the new Movement Imagery Questionnaire – 3 Second Version (MIQ-3S) along with the Vividness of Movement Imagery Questionnaire-2 (VMIQ-2) which measure the same three imagery abilities. Alpha coefficients and between scale Spearman correlations for internal, external, and kinesthetic abilities indicated items were internally consistent (α > 0.87) and established convergent validity (r > 0.69), respectively. MIQ-3S scale means ranged from 5.56 (SD = 1.10) to 5.98 (SD = 0.84), with no differences by sex. The three scales were not multicolinear as intra-scale correlations ranged from 0.47 to 0.61, supporting the three abilities were related, but separate constructs. A multi-trait multimethod confirmatory factor analysis (MTMM CFA), with sex invariance, was conducted to confirm the 3-factor structure of the MIQ-3S. Results from 396 healthy male ( n = 200) and female ( n = 196) adult college-aged students ( M = 21.91, SD = 2.37) indicated a correlated-traits correlated-uniqueness model provided the best fit to the data (CFI = 0.99; SRMR = 0.05; RMSEA = 0.03), while displaying sex invariance. These findings provide baseline data on college-aged, healthy adult participants providing reference data to those investigating imagery abilities among injured populations and practitioners interested in tracking individuals in rehabilitation. Highlights: The English MIQ-3S measures kinesthetic imagery, IVI and EVI perspectives. The 3-factor structure of the MIQ-3S was confirmed by MTMM CFA. The factor structure holds for both males and females. Movement method has no bearing on imagery abilities. Ease of imaging movement converges with imagery vividness.